What predicts PTSD 12 months after a road traffic accident? - Pires, Tânia Sofia Fernandes (2012)
Background: Discussions about Acute stress disorder (ASD) and Post-Traumatic Stress Disorder (PTSD) diagnosis criteria are an actual issue. The symptoms are similar but the period of time they evaluate is different. Our aim was to explore how the peri and posttraumatic reactions contribute to PTSD symptoms 12 months after a serious Road Traffic Accident (RTA). Methods: 101 RTA victims (76 male and 25 female) were evaluated 5 days, 4 and 12 months after RTA. Participants filled in an Acute Stress Disorder Questionnaire, a Personality Scale (NEO-FFI), the Peritraumatic Dissociation Experiences Questionnaire, the Ways of Coping Questionnaire, the Sickness Impact Profile and a Rating Scale for PTSD. Results: 32.7% of the participants had ASD, 58.4% had PTSD 4 months after the accident and 46.5% 12 months after the RTA. The hierarchical regression analysis revealed that peritraumatic dissociation, ASD, neuroticism and PTSD symptoms evaluated 4 months after the RTA and health status and general coping evaluated 12 months after the RTA explained 46.2% of the PTSD symptoms variance 12 months after the accident. The variables that give better contributions to the final model were neuroticism (4 months) and general coping (12 months). Discussion: Victims of serious accidents can have high prevalence of PTSD symptoms. Data showed that ASD and peritraumatic dissociation does not give an important contribution to explain PTSD 12 months after an RTA, when other variables are included in the model. Personality characteristics and coping strategies are significant predictors of PTSD among RTA victims and should be considered in prevention programs.